Polish Nonword Span (PNWSPAN): A new tool for measuring phonological loop capacity - Zychowicz, Katarzyna; Biedroń, Adriana; Pawlak, Mirosław (Glottodidactica, 2018)
The phonological loop, which is a component of working memory, is considered to be one of the most significant factors affecting L1 and L2 learning. In order to measure this construct properly, a reliable instrument in the native language of the participants is needed. The purpose of this paper is to present the Polish Nonword Span PNWSPAN, which is a tool constructed to measure verbal working memory, in particular the phonological loop, in the case of adults. The article presents the theoretical framework of the study and the process of construction of the test, namely its structure, scoring and validation procedure.